2017
DOI: 10.1177/0954410017733292
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of injection angle effects on shock vector control performance

Abstract: The present research paper attempted to utilize a computational investigation for optimizing the fluidic injection angle effects on thrust vectoring. Simulation of a convergent divergent nozzle with shock-vector control method was performed, using URANS approach with Spalart–Allmaras turbulence model. The variable fluidic injection angle is investigated at different aerodynamic and geometric conditions. The current investigation demonstrated that injection angle is an essential parameter in fluidic thrust vect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…SVC demonstrated a vectoring angle of 17.2 • and 17.6 • at NPR = 3 and 4.6. It was reported that the deflection angle increased with moving the injection location upstream and decreased with moving the injection location downstream of the nozzle [4]. At NPR = 4-10 and Secondary Pressure Ratio (SPR) = 1-2, with two different injection locations, the results showed that SPR positively influenced thrust vectoring parameters [5].…”
Section: Introductionmentioning
confidence: 94%
“…SVC demonstrated a vectoring angle of 17.2 • and 17.6 • at NPR = 3 and 4.6. It was reported that the deflection angle increased with moving the injection location upstream and decreased with moving the injection location downstream of the nozzle [4]. At NPR = 4-10 and Secondary Pressure Ratio (SPR) = 1-2, with two different injection locations, the results showed that SPR positively influenced thrust vectoring parameters [5].…”
Section: Introductionmentioning
confidence: 94%
“…The largest deflection angle was achieved when the injection location moved upstream and decreased when it moved downstream. The injection angle also played a vital role in the deflection angle [26]. The effect of secondary flow for an NPR = 4-10 with SPR = 1-2 at two different injection locations was investigated.…”
Section: Effect Of Npr and Sprmentioning
confidence: 99%
“…The primary flow then deflects through this shock wave, altering the vector angle and enhancing vector thrust. The effects of the NPR, secondary pressure ratio (SPR), and geometrical parameters on the performance of the SVC nozzle have been explored by a series of experiments and numerical studies [18][19][20][21][22][23][24][25][26][27]. The vector angle of an SVC nozzle increases monotonously in the absence of shock Due to its straightforward installation and implementation, the shock vector control (SVC) method is readily applicable in engineering practice [17].…”
Section: Introductionmentioning
confidence: 99%